2000
DOI: 10.1093/carcin/21.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite induces DNA-protein crosslinks and cytokeratin expression in the WRL-68 human hepatic cell line

Abstract: The induction of DNA-protein crosslinks (DPC) has been proposed as an indicator of early biological effects due to the fact that known or suspected carcinogens induce an increased proportion of proteins tightly bound to DNA. Arsenic, a human carcinogen, is reduced and methylated mainly in liver cells generating a number of intermediate reactive forms which could lead to the formation of DNA-protein crosslinks. The induction of DPC by arsenite [As(III)] was investigated in the WRL-68 human hepatic cell line, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Similarly UVR, particularly UVA, generates ROS in the skin also leading to oxidative DNA damage (11). Oxidative stress plays a significant role in UVR-induced skin carcinogenesis (12), and excessive ROS generation causes a range of DNA damages, including DNA strand breaks (13), DNA-protein cross-links (14), deletion mutations (15), and 8-hydroxyl-2Ј-deoxyguanine (8-OHdG) (16). 8-OHdG is a biomarker of oxidative stress and the major mutagenic form of oxidative DNA damage (17).…”
mentioning
confidence: 99%
“…Similarly UVR, particularly UVA, generates ROS in the skin also leading to oxidative DNA damage (11). Oxidative stress plays a significant role in UVR-induced skin carcinogenesis (12), and excessive ROS generation causes a range of DNA damages, including DNA strand breaks (13), DNA-protein cross-links (14), deletion mutations (15), and 8-hydroxyl-2Ј-deoxyguanine (8-OHdG) (16). 8-OHdG is a biomarker of oxidative stress and the major mutagenic form of oxidative DNA damage (17).…”
mentioning
confidence: 99%
“…Many endogenous compounds (e.g., metabolites of lipid peroxidation) as well as environmental agents are reactive with both DNA and proteins and thus can produce covalent linkage between these two types of macromolecules (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). DNA-protein crosslinks (DPCs) represent a relatively abundant form of DNA damage as evidenced by data indicating that the background level of DPCs in human white blood cells ranged from 0.5 to 4.5 per 10 7 bases (1).…”
mentioning
confidence: 99%
“…Seven of these proteins were identified as various cytokeratin isoforms. It has been reported that cytokeratins were among the proteins cross-linked to DNA after exposure to arsenite in WRL-68 human hepatic cells (Ramírez et al, 2000), suggesting the existence of DNAcytokeratin cross-links. Strikingly, we found that more proteins migrated to the bottom of the tube after the CsCl gradient centrifugation.…”
Section: Discussionmentioning
confidence: 99%